Elaboración e implementación del curso virtual de la asignatura de ciencias naturales para el noveno grado de educación general básica del colegio nacional “26 de Noviembre” de la ciudad de Zaruma periodo 2013-2014 - Toro Valarezo, María del Cisne (2014)
The present project Investigative, discussed the teaching resources used by the teacher for teaching since they still use traditional elements: printed book, guide study, marker, whiteboard, paperwork; This educational need is situated in the National College "November 26" located in the town of Zaruma, province of El Oro; exposed in the course of natural science for the ninth grade of basic General education, this is given by the lack of application of technologies of information and communication technology (ICT) in particular the use of virtual environments that are interactive teaching resources. Why was carried out the development and implementation of a virtual environment for the above-mentioned subject, using the Moodle Virtual Platform since this tool allows send monotonous classes and increase interactivity with a number of technological resources that presents for the improvement of the teaching-learning making the teacher and student to interact better, by actively participating and involving them in the new technological requirements framed in the field of education.